2015
DOI: 10.1002/chir.22422
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Degradation of Indoxacarb From Different Commercial Formulations Applied to Tea

Abstract: The stereoselective degradation of indoxacarb enriched with (+)-S-indoxacarb (S/R:70/30) was investigated in three typical green teas. A convenient and precise chiral method was developed and validated for measuring indoxacarb enantiomers in green tea. The developed method was based on high-performance liquid chromatography coupled with tandem mass spectrometry using a Chiralpak IC column. The stereoselective degradation of indoxacarb enantiomers showed that the (+)-S-enantiomer dissipated faster than the (-)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…In the original papers [21, 41 different compounds from 14 different pesticide classes are mentioned, with triazole fungicides and phenoxy herbicides being the two most represented classes (Figure 4). Dissipation studies and field-only experiments with no incubation experiments considered were left out [72,149,[156][157][158][159][160][161][162][163][164][165][166][167]. beta-cypermethrin soil laboratory incubation experiments under sterile and non-sterile conditions HPLC-VWD enantioselective degradation of beta-cypermethrin observed; different degradation rates observed for the four beta-cypermethrin isomers; EF variation noticed during the degradation process [143] beta-cypermethrinsoil laboratory incubation experiments under sterile and non-sterile conditions with acidic and alkaline matrices, and with racemic mixture and individual enantiomers HPLC-UV enantioselective degradation of racemic-beta-cypermethrin observed only in non-sterile soils; different degradation rates and half-lives observed for the four beta-cypermethrin isomers; no enantiomeric enrichment observed during degradation of individual enantiomers [144] Regarding the analytical methods used to quantify pesticides' enantiomers during biodegradation, the trend is clear and high-performance liquid chromatography with a diode array detector (HPLC-DAD) [117,122,123,126,128,134,135,140,152] and an ultraviolet detector (UV) [120,129,132,136,138,141,144,146,…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 99%
“…In the original papers [21, 41 different compounds from 14 different pesticide classes are mentioned, with triazole fungicides and phenoxy herbicides being the two most represented classes (Figure 4). Dissipation studies and field-only experiments with no incubation experiments considered were left out [72,149,[156][157][158][159][160][161][162][163][164][165][166][167]. beta-cypermethrin soil laboratory incubation experiments under sterile and non-sterile conditions HPLC-VWD enantioselective degradation of beta-cypermethrin observed; different degradation rates observed for the four beta-cypermethrin isomers; EF variation noticed during the degradation process [143] beta-cypermethrinsoil laboratory incubation experiments under sterile and non-sterile conditions with acidic and alkaline matrices, and with racemic mixture and individual enantiomers HPLC-UV enantioselective degradation of racemic-beta-cypermethrin observed only in non-sterile soils; different degradation rates and half-lives observed for the four beta-cypermethrin isomers; no enantiomeric enrichment observed during degradation of individual enantiomers [144] Regarding the analytical methods used to quantify pesticides' enantiomers during biodegradation, the trend is clear and high-performance liquid chromatography with a diode array detector (HPLC-DAD) [117,122,123,126,128,134,135,140,152] and an ultraviolet detector (UV) [120,129,132,136,138,141,144,146,…”
Section: Biodegradation Studies Of Chiral Pesticidesmentioning
confidence: 99%
“…Similar results were obtained in different crop plant samples. For example, S‐ indoxacarb was degraded faster than R‐ indoxacarb in cabbage (Sun et al, ), commercial teas (Zhang et al, ), cucumber and tomato (Wang et al, ). Notably, similar T 1/2 and EF values were obtained in the two regions in our study, demonstrating that the enantioselective of indoxacarb on rice plants was slightly affected by the climate and growth conditions and greatly affected by the rice itself.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Zhang, Hu, et al () demonstrated that S‐ (+)‐indoxacarb is preferentially degraded in two alkaline soils while R‐ (−)‐indoxacarb is preferentially degraded in acidic soil; Sun et al found that R‐ (−)‐indoxacarb degrades faster in Beijing cabbage, but the opposite result is obtained in the Anhui cabbage (Sun et al, ). Moreover, some reports have proven that S‐ indoxacarb is preferentially degraded over R‐ indoxacarb in cucumber, tomato (Wang et al, ), water (Zhang et al, ), soil (Sun et al, ) and tea (Zhang et al, ). In those reports, the degradation of indoxacarb enantiomers exhibits individual differences, and their half‐lives vary in different matrices.…”
Section: Introductonmentioning
confidence: 99%
“…Indoxacarb (see Figure for structure), a new chiral oxadiazine pro‐insecticide, being converted into the active compound by removal of a CO 2 Me in the insect gut (discovered and developed by the E.I. DuPont Company), has shown to possess high activity, commercial availability, and environmental compatibility to administered to lepidopteran and hemipteran pests . An essential characteristic of indoxacarb is its novel bioactivation mechanism by blocking insect voltage‐dependent sodium channels, which is associated with high insecticidal activity .…”
Section: Introductionmentioning
confidence: 99%